2008
DOI: 10.1227/01.neu.0000317315.48612.b1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Traumatic Peroneal Nerve Lesions

Abstract: Peroneal nerve lesions lacking regenerative signs should be explored. A functionally useful result (M >or=4) was achieved in 72% of the patients with either external or internal neurolysis and in 28% of the patients after a nerve graft procedure. Patients in whom nerve surgery failed to reconstitute useful foot lift need to be evaluated for their suitability to undergo a tendon transfer procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 27 publications
0
49
0
7
Order By: Relevance
“…The overall good outcomes (M4 or greater) across the 1577 repairs in 28 studies [1][2][3][4][5][6][7]10,[12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] amounted to slightly more than 45 percent. If studies from only the twenty-first century are taken into account, this percentage rises to slightly more than 50.2 percent (n = 1111); this is a significant improvement when compared with studies performed in the twentieth century, which was 38.7 percent (n = 466).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall good outcomes (M4 or greater) across the 1577 repairs in 28 studies [1][2][3][4][5][6][7]10,[12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] amounted to slightly more than 45 percent. If studies from only the twenty-first century are taken into account, this percentage rises to slightly more than 50.2 percent (n = 1111); this is a significant improvement when compared with studies performed in the twentieth century, which was 38.7 percent (n = 466).…”
Section: Resultsmentioning
confidence: 99%
“…1,2,[4][5][6][7]10,[12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Table 3 shows the 25 studies 1,2,4-7,10,12-14,17-31 included in this section with 1254 surgical repairs. Studies showed 80 percent of patients (n = 359) achieving M4 or above with neurolysis, while end-to-end suture yielded a good outcome in 37 percent of patients (n = 464) and interfascicular nerve grafting followed closely behind with 36 percent (n = 431).…”
Section: Repair Typementioning
confidence: 99%
See 2 more Smart Citations
“…One study suggests operative exploration is indicated in a recognized nerve laceration or any open or closed injury that fails to show recovery by clinical or electromyographic examination 3 months or more after injury [22]. Nerve grafting is rarely successful when grafts are greater than 6 cm in length [7,17,18,22]; therefore, in traumatic longitudinal nerve traction injuries, in which the nerve injury is lengthy, nerve grafting may not be the optimal treatment. Posterior tibial tendon transfers and their variants (Bridle procedure, Riordan transfer) are a commonly used treatment for foot drop [6].…”
Section: Introductionmentioning
confidence: 99%